Expression of P62 in hepatocellular carcinoma involving hepatitis B virus infection and aflatoxin B1 exposure. (21st September 2017) - Xiang, Xiao; Qin, Hong‐Gui; You, Xue‐Mei; Wang, Yan‐Yan; Qi, Lu‐Nan; Ma, Liang; Xiang, Bang‐De; Zhong, Jian‐Hong; Li, Le‐Qun
Abstract: This study aims to clarify the relationship and mechanism between expression of autophagy‐related protein P62 and prognosis of patients with hepatocellular carcinoma (HCC) involving chronic hepatitis B virus (HBV) infection and aflatoxin B1 (AFB1) exposure. HCC patients who underwent resection were divided into three groups: HBV(+)/AFB1(+) ( n  = 26), HBV(+)/AFB1(−) ( n  = 68), and HBV(−)/AFB1(−) ( n  = 14). The groups were compared in terms of mRNA and protein levels of P62, disease‐free survival (DFS), and overall survival (OS) and the expression of NRF2, Nqo1, and AKR7A3 in P62 high‐expression and low‐expression group. HBV(+)/AFB1(+) group has lower DFS and OS, and higher P62 expression than in the other two groups. P62 expression generally correlated with elevated NRF2 and Nqo1 expression, and reduced AKR7A3 expression. Patients expressing high levels of P62 showed significantly lower DFS and OS rates than patients expressing low levels. HCC involving HBV infection and AFB1 exposure is associated with relatively high risk of tumor recurrence, and this poor prognosis may relate to high P62 expression. High P62 expression activates the NRF2 pathway, promotes tumor recurrence. The downregulation of AKR7A3 also reduced liver detoxification of aflatoxin B1. Abstract : HCC involves HBV infection and AFB1 exposure has a poor prognosis and high P62 expression. High P62 expression activates the NRF2 pathway, promotes tumor recurrence, downregulates AKR7A3, and reduces liver detoxification of aflatoxin B1.